Foodborne Pathogen Survival in Commercial Aloreña de Málaga Table Olive Packaging - Romero-Gil, Verónica; Medina, Eduardo; Garrido-Fernández, Antonio; Arroyo-López, Francisco Noé (Frontiers in Microbiology, 2018)
This study presents an approach to determine the survival of diverse foodborne pathogens (Escherichia coli, Staphylococcus aureus, Listeria monocytogenes, and Salmonella enterica) in three Aloreña de Málaga table olive commercial presentations (fresh green, traditional, and cured olives). The microbial survival in this green natural table olive speciality was fit using a log-linear regression model implemented in GInaFIT. The contents of sugars, phenolic compounds, additives, salt, pH, and levels of autochthonous microorganisms differed among presentations and affected the survival of microorganisms. The inoculated initial populations of pathogens (7-8 log10 CFU/mL brine) decreased rapidly and, 48 h after inoculation, their counts were always below the detection limit (<1.3 log10 CFU/mL), except for S. aureus in the fresh green presentation which was 5.0 log10 CFU/mL. The highest maximum death rates (kmax) and lowest periods for 4 log10 reductions (4Dr) were observed in cured olives but decreased and increased, respectively, from the traditional to the fresh green presentations. L. monocytogenes and S. aureus were the most resistant species. The multivariate analysis showed that high concentrations of compounds released from the olives (sugars and phenols) were positively associated to 4Dr and negatively to kmax. Conversely, the presence of preservatives reduced 4Dr. This study, executed in commercial products, pointed out that packaged table olives are adverse habitats for foodborne pathogens with their effects being presentation dependent. The survival of S. aureus was particularly long in green fresh Aloreña de Málaga table olives packaged without preservatives; therefore, its changes in this presentation still requires further in-deep research.